Indonesia’s women; Diversity and dynamics - Niehof, Anke (UI Scholars Hub, 2023)
The study of Indonesian women inevitably involves methodological questions, a prime one being whether Indonesian women as a category form a meaningful object of study. In edited volumes on Indonesian women, the contributions usually form a mosaic of different kinds of Indonesian women, defined by variables such as ethnicity, class, residence, or historical time. This raises questions about diversity and difference and the applicability of specific findings to Indonesian women in general. Taking as a point of departure that it is useful to treat Indonesian women’s studies as one field of study, I explore these issues in relation to women’s agency and empowerment. First, I do so by applying a system’s approach to a case which I know best from my own fieldwork, that of women in a Madurese fishing community. Second, I use an intersectional approach to explore the subject of Indonesian women and social change, focusing on the aspects of family and food, and urbanization. Finally, I interweave the two parts and draw conclusions on the resilience of traditional values in the family food domain and on the impact of women’s paid work, but I also point at many remaining questions for further research.